Performing the Psalms - Bland, Dave (St. Louis, Mo. Chalice Press, 2005)
Part I: Essays on performing the Psalms -- Psalms in narative performance / Walter Brueggemann -- The Psalms as limit expressions / Walter Brueggemann -- Greed, grace, and gratitude : an approach to preaching the Psalms / J. Clinton McCann, Jr. -- Preaching community laments : responding to disillusionment with God and injustice in the world / John Mark Hicks -- The New Testament preaches the Psalms : problems and possibilities / Ronald Cox -- Reading the Psalms for preaching : fictive plot / Paul Scott Wilson -- Part II: Sermons on performing the Psalms -- Like a child at home : Psalm 23 and John 10:1/10 / J. Clinton McCann, Jr. -- Beauty : Psalm 27 / James Howell -- Though mountains shake in the sea : Psalm 46 / Mark Love -- The goodness of God : Psalm 73 / Dave Bland -- Going to church in the Psalms : Psalm 89 / Mark Love -- Dust in the space between : Psalm 103 / Jeff M. Christian -- Sing to the Lord a new song? : trouble leaving the lament : Psalm 146 / David Fleer.
Keywords: Bible -- O.T -- Psalms -- Criticism, interpretation, etc